2021
DOI: 10.21203/rs.3.rs-1001813/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D and the risk of latent tuberculosis infection: a meta-analysis

Abstract: Objective Latent tuberculosis infection (LTBI) may be a risk of developing tuberculosis (TB) and thus a health hazard. The aim of this meta-analysis is to explore the association between vitamin D and LTBI. Methods Databases including PubMed, Embase, Scopus, and ProQuest were electronically searched to identify observational or interventional studies that reported the association between vitamin D and LTBI. The retrieval time is limited from inception to September 2021. Two reviewers independently screened l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Both industrialized and developing countries have reported deficient vitamin D in their population, yet it is a known risk factor for poor immune systems 3 7 . Over the years, evidence has shown that the vitamin D pathway plays a role in the immune system, where immune cells, including macrophages, augment antimicrobial peptide expression, which regulates the inflammatory response 8 , 9 . Cathelicidin antimicrobial peptide is a defense molecule that is involved in both innate and adaptive immunity and modulates infections through Toll-like receptor responses 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Both industrialized and developing countries have reported deficient vitamin D in their population, yet it is a known risk factor for poor immune systems 3 7 . Over the years, evidence has shown that the vitamin D pathway plays a role in the immune system, where immune cells, including macrophages, augment antimicrobial peptide expression, which regulates the inflammatory response 8 , 9 . Cathelicidin antimicrobial peptide is a defense molecule that is involved in both innate and adaptive immunity and modulates infections through Toll-like receptor responses 10 .…”
Section: Introductionmentioning
confidence: 99%